Electrocapacitive Deionization: Mechanisms, Electrodes, and Cell Designs. (26th February 2023) - Sun, Kaige; Tebyetekerwa, Mike; Wang, Chao; Wang, Xianfen; Zhang, Xiwang; Zhao, Xiu Song
Abstract: Capacitive deionization (CDI) is an emerging water desalination technology for removing different ionic species from water, which is based on electric charge compensation by these charged species. CDI is becoming popular because it is more energy‐efficient and cost‐effective than other technologies, such as reverse osmosis and distillation, specifically in dealing with brackish water having low or moderate salt concentrations. Over the past decade, the CDI research field has witnessed significant advances in the used electrode materials, cell architectures, and associated mechanisms for desalination applications. This review article first discusses ion storage/removal mechanisms in carbon and Faradaic materials aided by advanced in situ analysis techniques and computations. It then summarizes research progress toward electrode materials in terms of structure, surface chemistry, and composition. More still, it discusses CDI cell architectures by highlighting their different cell design concepts. Finally, current challenges and future research directions are summarized to provide guidelines for future CDI research. Abstract : More than half of the global population is experiencing water scarcity. Capacitive deionization (CDI) reveals tremendous potential in water desalination to solve this global challenge. This review provides a comprehensive discussion on the recent progress of CDI in water desalination, with a focus on CDI ion storage mechanisms, design and optimization of electrode materials, and CDI cell architectures.